Autobiography or my Experiments with Truth - "Gandhi, Mohandas Karamchand" (New Delhi, 2006)
A face we see all around us-everyday, even if we do not visit government offices. Teachings people swear by and entertained to in films. We still see his style being imitated in the political circles-that is Mohandas karamchand Gandhi. One of the influence rs of the millennium, the half naked Indian man who shook the mightiest empire of the modern world, has a story to tell-his story. An autobiography of Gandhi, the book starts with his birth and ends with his experiences till 1921. The original manuscript was written in weekly installments in Gujarati by Gandhi and was published weekly in his journal navjivan from 1925 to 1929. It was later translated by mahadev desai in English, which too was published in installments in his other journal young india. Unlike most autobiographies or biographies, Gandhis autobiography speaks about his fears, regrets, failures, struggles and all that went through his mind while initiating and going through the experiments he conducted, in his and his immediate familys lives. Gandhi hides nothing from his readers, he wants his experiences and experiments to reach out to people so that their life becomes worth living. Gandhi, through his lucid and simple style of writing, honest opinions and candid narrations, takes us to the man who was mahatma in his thoughts and actions.
Keywords: M.K.Gandhi-Autobiography